2017
DOI: 10.1186/s12905-017-0403-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and a prediction model for lower limb lymphedema following lymphadenectomy in gynecologic cancer: a hospital-based retrospective cohort study

Abstract: BackgroundLower limb lymphedema (LLL) is a chronic and incapacitating condition afflicting patients who undergo lymphadenectomy for gynecologic cancer. This study aimed to identify risk factors for LLL and to develop a prediction model for its occurrence.MethodsPelvic lymphadenectomy (PLA) with or without para-aortic lymphadenectomy (PALA) was performed on 366 patients with gynecologic malignancies at Yaizu City Hospital between April 2002 and July 2014; we retrospectively analyzed 264 eligible patients. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 53 publications
4
69
0
4
Order By: Relevance
“…It is possible that only few participants of the study reported the infection symptoms of the lower limbs (4%), which may decrease the item homogeneity. The rate of limb skin infection is similar to that reported by Kuroda et al, () study that the prevalence rate of skin infection for lower limbs is 4%–8% among gynaecological cancer women (Kuroda et al, ). However, the rate of limb infection is lower than that (10%) reported in the study of Devoogdt et al ().…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is possible that only few participants of the study reported the infection symptoms of the lower limbs (4%), which may decrease the item homogeneity. The rate of limb skin infection is similar to that reported by Kuroda et al, () study that the prevalence rate of skin infection for lower limbs is 4%–8% among gynaecological cancer women (Kuroda et al, ). However, the rate of limb infection is lower than that (10%) reported in the study of Devoogdt et al ().…”
Section: Discussionsupporting
confidence: 86%
“…Lower limb lymphoedema (LLL), a chronic and progressive condition, is a common complication among women with gynaecological cancer who undergo lymphadenectomy or radiation therapy (Lockwood‐Rayermann, ). The LLL has a variation in its time of occurrence, with the median time after surgery from 6 months to 13.5 years (Abu‐Rustum et al, ; Kuroda et al, ; Ohba et al, ). The prevalence rate of LLL ranged from 11% to 38% in gynaecological cancer patient (Achouri et al, ; Tada, Teramukai, Fukushima, & Sasaki, ; Todo et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davon konnten nach inhaltlicher Analyse der Abstracts 45 Artikel identifiziert werden, die sich vordringlich mit ätiologischen Faktoren, Komorbiditäten oder Folgeerkrankungen des Lymphödems befassen. 24 Arbeiten (53 %) davon thematisierten sekundäre Lymphödeme nach Mammakarzinom , 15 Arbeiten (33 %) sekundäre Lymphödeme nach anderen gynäkologischen Malignomen [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. 3 Arbeiten (7 %) betrachteten sekundäre Lymphödeme bei nichtgynäkologischen Erkrankungen (Kopf-Hals-Karzinom, Melanom, Lymphangioleiomyomatose).…”
Section: Hintergrundunclassified
“…Beinlymphödeme nach Behandlung gynäkologischer Tumoren zeigen vergleichbare therapieabhängige Risikofaktoren. Mehrere Autoren geben an, dass hier bereits Übergewicht mit einem BMI über 25 als Komorbidität einen unabhängigen Risikofaktor für die Entstehung eines Lymphödems darstellt [29,40]. Weitere Komorbiditäten wurden nicht dargestellt.…”
Section: Hintergrundunclassified